Sociolinguistic aspects of address terms based on Kazakh consanguine kinship system - A. Muldagaliyeva; K. A. Aisultanova; Z. K. Madiyeva (Хабаршы. Психология және социология сериясы, 2022)
The Kazakh society, being traditional in nature, strictly regulates the behavior of its members in many spheres of life, including family communication. The usage of kinship address terms to refer to relatives as well as nonrelatives indicates the uniqueness of the Kazakh culture. Kinship address terms are powerful means of creating and maintaining solidarity among not only members of a kin community but the whole society. In the Kazakh language, there is a plethora of address terms young people use to refer to the members of their family and сlose relatives. The present article is aimed to investigate the address terms that modern younger generations of the Kazakhs use to refer to their parents, siblings, grandpar- ents, uncles, aunts and cousins, and nonkins to determine in what way kinship address terms regulate the communicative behavior of the younger generation and formation of their live values. The analysis of data obtained through on-line survey, observation and face-to-face interviews yielded valuable informa- tion on the usage of address terms within a nuclear family and close consanguine relatives. The research revealed a strong family orientation of today’s Kazakh young people. A peculiarity of Kazakh address terms is a wide use of «Russianized» and Russian kinship terms by the modern Kazakh youth due to two factors – intercultural communication and the bilingual situation in Kazakhstan. Investigation of Kazakh consanguine kinship terms of address employed by the younger generation theoretical and practical sig- nificance. It enabled to demonstrate the links between language use, social relations and cultural values.